Africa's Oil Abundance and External Competitiveness : Do Institutions Matter? - Qureshi, Mahvash (IMF Working Papers; Working Paper, 2008)
This paper examines the structural competitiveness of oil-rich economies in sub-Saharan Africa relative to other major oil-exporting developing countries, and investigates reasons for systematic differences in the non-oil export performance across these economies. The analysis reveals that oil-rich Africa lags behind other oil-exporters in terms of diversification, global market share and the overall investment climate. The poor performance of their nonoil sector can be largely attributed to weak infrastructure and institutional quality. The results also show that institutional quality is a significant determinant of the extent to which oil abundance affects the competitiveness of the non-oil sector; thereby explaining the divergent experiences of oil-rich economies across the world. This implies that oil wealth does not necessarily weaken the non-oil tradable sector; countries may mitigate the impact of Dutch disease and benefit from oil booms if revenues are used prudently to reduce oil dependence.